Chronic headaches and middle meningeal artery embolization. (22nd April 2021) - Catapano, Joshua S; Karahalios, Katherine; Srinivasan, Visish M; Baranoski, Jacob F; Rutledge, Caleb; Cole, Tyler S; Ducruet, Andrew F; Albuquerque, Felipe C; Jadhav, Ashutosh P
Abstract : Background: The middle meningeal artery (MMA) has been implicated in chronic headaches, but no studies have examined the relationship between MMA embolization and headaches. Methods: Patients treated with MMA embolization for a chronic subdural hematoma (cSDH) between January 1, 2018, and December 31, 2020, were retrospectively assessed. Patients with a Glasgow Coma Scale (GCS) score of 15 at discharge received a follow-up telephone call to assess their history of chronic headache, defined as a headache ≥2 years before the cSDH and symptoms ≥2 days/month. A Headache Impact Test (HIT-6) was performed during the follow-up telephone call. The primary outcome was resolution or improvement of headaches after embolization. Results: Of 76 patients undergoing MMA embolization for a cSDH during the study period, 56 (74%) had a discharge GCS score of 15. Of these 56 patients, 46 (82%) responded to a follow-up telephone call and were analyzed (mean [SD] age 68 [11] years; 36 [78%] men and 10 [22%] women). Nine (20%) reported chronic headaches before embolization. With a mean (SD) follow-up of 489 (173) days, eight of the nine patients reported improvement of chronic headaches, with seven having complete resolution. For these nine patients, the mean (SD) HIT-6 score was significantly higher before embolization than after embolization (64 [7.1] vs 40 [9.1], p<0.001). Conclusion: In patients with chronic headaches who underwent MMA embolization for a cSDH, the majority reported improvement of headaches after the procedure. Future prospective studies are warranted to assess the usefulness of MMA embolization to treat chronic headaches.